'My countrymen have never disappointed me': Politics of service in Modi's speeches during Covid-19. (June 2022) - Sambaraju, Rahul
Abstract: In this paper I study discursive practices of Indian Prime Minister Narendra Modi during the COVID-19 pandemic. In response to the pandemic, political leadership across the globe had to take tough decisions such as restrictions on the social and personal lives of individuals. This meant addressing concerns over ensuring compliance with these restrictions. I examine how Modi managed these concerns in his communication with the Indian polity over TV and radio broadcasts. I do so in instances where Modi gave specific instructions about following restrictions or other COVID appropriate behaviours. Using discourse analysis, I analyse data from two prominent ways of communicating in the pandemic, Mann Ki Baat and addresses to the nation. Analyses show that Modi developed two sets of non-electoral relations across his communication, which treated compliance as normatively expected: a) between Modi and Indians and b) among Indians themselves. These relations made way for treating audiences as those who are in specific social roles where duty and service were normative. Instructions and their compliance were embedded in these roles and treated as expected and consequently moral acts. Modi's discursive practices worked to perform a politics of service and duty, where compliance is ultimately treated as expected service.